THE ANALYSIS OF ANTI-CORRUPTION BEHAVIOR (CASE STUDY: BATAM CENTRAL BUREAU OF STATISTIC (BPS) SERVICES) - Raja Dachroni; Ady Muzwardi (Universitas Pancasakti Tegal, 2017)
Anti-Corruption Behaviour Survey is a national programme that measures individual Indonesians' anti-corruption knowledge, attitudes and experiences. The Survey also assesses the nationwide implementation of the National Anti-Corruption Strategy for the Prevention and Eradication of Corruption (STRANAS-PPK) to establish a culture of zero tolerance for corruption in the country. A key activity in support of this assessment is to set the baselines for the STRANAS-PPK anti-corruption strategies.This study is aimed to analyze the mainly determined the anti-corruption behavior on Batam Central Bureau of Statistic (BPS). This research used descriptive statistical analysis method. Data collected in this research use interview technique, observation, and questioner. This sample of this research has been taken from government institution/ Regional Work Unit (SKPD)/ Research and Education Institution : National and International/ Mass Media/ Banking/ Private.The result of the analysis indicates that Batam Central Bureau of Statistic (BPS) is relatively high compared with the average score of hope, The low average score of expectation shows that anti-corruption conditions in Batam Central Bureau of Statistic (BPS) services are clean enough